Analisis Gugatan Wanprestasi Dalam Jual Beli Rumah Dan Tanah Berdasarkan Putusan Pengadilan Negeri Semarang No.346/Pdt.G/2014/Pn.Smg. - Sadat, Anwar; Kornitin, Roa; Sukatama, Susandhi; Darwin; Agus Jaya, Kurnia; Luthfi Hilmy, Mohammad (PT Elaborium Elevasi Indonesia, 2025)
This study discusses the analysis of breach of contract claims in home and land sale transactions, focusing on the legal considerations in the Semarang District Court Decision No. 346/Pdt.G/2014/PN.Smg. The aim of this research is to identify the factors influencing the judge’s decision in granting the claim. This research uses a normative juridical method, conducted through a literature study to analyze secondary data, including primary and secondary legal materials. The collected data is analyzed qualitatively using a descriptive approach. The research findings indicate that the claim was granted because the defendant failed to fulfill the obligation of delivering the land certificate to the plaintiff. The judge’s consideration emphasized that the defendant violated the agreement by failing to complete the transaction in front of a Notary or Land Deed Official (PPAT) in Semarang. The legal consequence is that the defendant is required to implement the agreement, including processing the ownership certificate in the plaintiff's name. This decision refers to Article 1234 of the Civil Code (KUHPerdata).